2014
DOI: 10.2337/db13-1123
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Incorporation of Fatty Acids Into Triacylglycerol in Myotubes From Obese Individuals With Type 2 Diabetes

Abstract: Altered skeletal muscle lipid metabolism is a hallmark feature of type 2 diabetes (T2D). We investigated muscle lipid turnover in T2D versus BMI-matched control subjects (controls) and examined whether putative in vivo differences would be preserved in the myotubes. Male obese T2D individuals (n = 6) and BMI-matched controls (n = 6) underwent a hyperinsulinemic-euglycemic clamp, VO 2 max test, dual-energy X-ray absorptiometry scan, underwater weighing, and muscle biopsy of the vastus lateralis.14 C-palmitate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
14
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 47 publications
5
14
1
Order By: Relevance
“…For instance, myotubes derived from obese individuals with T2D retain the impaired mitochondrial function that was observed in vivo (61,62). Consistent with these findings, data from Hulver and colleagues (65), along with some of our own work, have demonstrated that myotubes of nondiabetic individuals with severe obesity and those from obese T2D individuals retained an abnormal lipid partitioning similar to that observed in their muscle tissue (65,66). Work by Nikolic et al (67) demonstrated that chronic low-frequency electrical pulse stimulation was sufficient to induce a more oxidative phenotype in lean myotubes (and hence mimic an exercise contraction)-which is consistent with our previous findings that demonstrated an improved insulin responsiveness and lipid metabolism after a pharmacological exercise mimetic in lean human myotubes (68).…”
Section: In Vitro Studiessupporting
confidence: 66%
“…For instance, myotubes derived from obese individuals with T2D retain the impaired mitochondrial function that was observed in vivo (61,62). Consistent with these findings, data from Hulver and colleagues (65), along with some of our own work, have demonstrated that myotubes of nondiabetic individuals with severe obesity and those from obese T2D individuals retained an abnormal lipid partitioning similar to that observed in their muscle tissue (65,66). Work by Nikolic et al (67) demonstrated that chronic low-frequency electrical pulse stimulation was sufficient to induce a more oxidative phenotype in lean myotubes (and hence mimic an exercise contraction)-which is consistent with our previous findings that demonstrated an improved insulin responsiveness and lipid metabolism after a pharmacological exercise mimetic in lean human myotubes (68).…”
Section: In Vitro Studiessupporting
confidence: 66%
“…A prime example is that of the athlete's paradox , whereby both insulin resistant T2D individuals and endurance trained athletes possess high levels of IMCL in vivo yet differ greatly along the insulin sensitivity spectrum. Prior reports investigating lipid droplet coat proteins comparing myotubes from lean individuals versus those with T2D showed that there was no difference in basal protein levels of perilipin 2, perilipin 3, perilipin 5, or adipose triglyceride lipase (ATGL) . Kitzmann et al showed that there was no difference in basal activity for 5′ adenosine monophosphate‐activated protein kinase (AMPK) or its downstream target acetyl‐CoA carboxylase (ACC) in myotubes taken from controls versus individuals with T2D .…”
Section: Discussionmentioning
confidence: 99%
“…HepG2 cells were grown in MEM supplemented with 10% FCS, sodium pyruvate and non-essential amino acids and pen/strep as described [18]. Collection and differentiation of human primary myotubes have been described previously [19]. Growth and differentiation of human primary differentiated adipocytes have been described before [20], however, modifications have been applied to the original protocol.…”
Section: Cell Culturementioning
confidence: 99%